2016
DOI: 10.1108/bfj-12-2015-0496
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge, halal quality assurance practices and commitment among food industries in Malaysia

Abstract: Purpose-The purpose of this paper is to assess the level of knowledge, halal dietary quality assurance practices, and commitment among food industries in the implementation of halal in Malaysia. Besides, the study was based on two categories that are considered major contributors in the chain of halal food sector in Malaysia which are the multinational, and small medium enterprise (SME).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 22 publications
2
37
0
2
Order By: Relevance
“…Hence, they have a positive image of Bakso Wagyu in their minds. The results of this research are supported by earlier research, such as Othman, Shaarani, and Bahron (2016) have revealed that customers tend to choose brands that are well known because they feel safe with something known and think the brand is likely to be reliable and the quality that can be accounted for.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Hence, they have a positive image of Bakso Wagyu in their minds. The results of this research are supported by earlier research, such as Othman, Shaarani, and Bahron (2016) have revealed that customers tend to choose brands that are well known because they feel safe with something known and think the brand is likely to be reliable and the quality that can be accounted for.…”
Section: Resultssupporting
confidence: 82%
“…This means that the brand is an asset owned by the company as a sign of the business or product or also the services that the company has to make it easily recognizable by the customer and also as a differentiator with the products or services of other companies. Othman, Shaarani, and Bahron (2016) have said that a famous and trusted brand is an invaluable asset. Brands develop into the largest source of assets and are important factors in the company's marketing activities.…”
Section: Growth Of Halal Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here the government must recognize false Halal certification unions and issue a regulation with removing the unlawful operations. (4) Many Halal certification organizations trigger misperceptions among customers about their legitimacy and at times operate as a blockade in international trade (REG1); this can be mitigated by developing the synchronized Halal certification unions Othman et al (2016) recommend.…”
Section: Ijibe (International Journal Of Islamic Business Ethics)mentioning
confidence: 99%
“…This is reflected by recent academic work especially on Halal integrity and Islamic economy reports suggesting Tayyib to be a new trend and a value adding factor in marketing Halal products. [6][7][8][9][10] The Tayyib concept has a wide scope under which various food sector issues could be discussed, [11][12][13] however, this paper will cover the aspects of food safety. For a Muslim consumer a food is safe for consumption if it complies with requirements set by the fundamental sources of Halal and Haraam Jurisprudence, namely the Quran and the Sunnah.…”
Section: Introductionmentioning
confidence: 99%